2012
DOI: 10.1063/1.4730435
|View full text |Cite
|
Sign up to set email alerts
|

Low resistance Ti Ohmic contacts to 4H-SiC by reducing barrier heights without high temperature annealing

Abstract: Ti Ohmic contacts to relatively highly doped (1 × 1018 cm−3) n-type 4H-SiC have been produced, without high temperature annealing, by means of low temperature electronic cyclotron resonance microwave hydrogen plasma pre-treatment (HPT) of the SiC surface. The as-deposited Ti/4H-SiC contacts show Ohmic properties, and the specific contact resistance obtained is as low as 2.07 × 10−4 Ω·cm2 after annealing at low temperatures (400 °C). This is achieved by low barrier height at Ti/SiC interface, which could be att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 32 publications
1
21
1
Order By: Relevance
“…In this case, q Bn largely depends on q m rather than on interface state density (D it ). [6,13] Fig. 4 shows q Bn as a function of q m (the TiC, Ti, Ni, and Pt contacts [6,16]) for RCA, HPT, and HPT and 600 • C AT.…”
Section: Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, q Bn largely depends on q m rather than on interface state density (D it ). [6,13] Fig. 4 shows q Bn as a function of q m (the TiC, Ti, Ni, and Pt contacts [6,16]) for RCA, HPT, and HPT and 600 • C AT.…”
Section: Samplesmentioning
confidence: 99%
“…[6,13] Fig. 4 shows q Bn as a function of q m (the TiC, Ti, Ni, and Pt contacts [6,16]) for RCA, HPT, and HPT and 600 • C AT. In general, q Bn is expressed as [13] …”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminum (Al) and titanium (Ti) were used as metallization materials. Earlier research showed that these metals will form an ohmic contact to the doped poly-SiC layers employed in this work [5], [26], [27]. A post-deposition annealing process in a nitrogen environment was followed to relieve the strain and improve the contact property at the metalsemiconductor interface.…”
Section: Si Substrate Sio2mentioning
confidence: 99%
“…While the surface after plasma treatment was more reactivity to adsorb the atmospheric oxygen atoms to form GeOx. Interface states caused by the contaminants [26] and dangling bonds [27,28], were proposed to be responsible for the severe FLP effect in the metal/Ge contacts. The contaminants were removed and some dangling bonds was occupied by O atoms, hence, the SBH was lowered, as shown in Fig.…”
Section: The Model For the N2 Plasma Passivationmentioning
confidence: 99%